Odpowiedzi

2010-04-11T13:32:18+02:00
A) y=2t-3x
b) y=2(x-1)
c) y=x-1/2
d) y=2/x-1
f) P=1/3(a²+2ax)

a) x=2t-y/3
b) x= y/2 + 2
c)x=2y+1
d - f nie wiem
2010-04-11T13:33:20+02:00
A) y=2t-3x
2t-3x=y
-3x=y-2t
x=y-2t/-3
b) y=2(x-1)
2x-2=y
2x=y+2
x=y+2/2
c) y=x-1/2
x-1/2=y
x=y+1/2

d) y=2/x-1
2/x-1=y całośc pomnożyć przez x
2-x=xy
-x-xy=-2 pomnożyc całośc przez (-1)
x+xy=2
x(1+y)=2
x=2/1+y
f) P=1/3(a²+2ax)
a²/3+ 2ax/3=P całośc pomnożyc przez 3
a²+2ax=3P
2ax=3P-a²
x=3P-a²/2a
2010-04-11T13:40:38+02:00
A) y=2t-3x
y-2t=-3x / :(-3)
- y+ 2t/3 =x

b) y=2(x-1) /:(2)
y/2 = x-1
y/2 +1 = x

c) y=x-1/2
y + 1/2 = x

d) y=2/x-1 / ×(x-1)
y(x-1)=2 /: y
x-1= 2/y
x = 2/y +1

f) P=1/3(a²+2ax) / × 3
3P = a²+2ax
3P-a² = 2ax / : (2a)
3P-a²/ 2a = x